Erudizione e medicina nelle lettere di Jacopo Corbinelli a Gian Vincenzo Pinelli (1579-1587) (Quaderni di Gargnano, 2018)
This study of the letters of Jacopo Corbinelli to Gian Vincenzo Pinelli from between 1579 and 1587 shows how they easily mix erudition with knowledge of science and the art of medicine. The correspondence contains plenty of detail about the bibliographical interests of the two great humanists, but also mentions scientific literature and publications on the plague, along with references to Corbinelli’s relationship with the renowned French physician Bonaventure Granger and, especially, the Italian physician-philosopher Girolamo Mercuriale. The frequency of references to Corbinelli’s health and private affairs increases over the years, with the result that the later letters exemplify certain aspects of the culture of the time and, most interestingly, illuminate some of the Aristotelian beliefs that underpinned the late Renaissance understanding of medicine.
Keywords: Jacopo Corbinelli; Gian Vincenzo Pinelli; medicina rinascimentale; Girolamo Mercuriale